Engagement Elements for Mobile Augmented Reality Application - Jaffar Baker, Esraa; Aida Abu Bakar, Juliana; Nasir Zulkifli, Abdul (International Journal of Engineering and Technology, 2018)
Mobile Augmented Reality is a form of Augmented Reality which allows users to interact with the augmented environment in a social context. However, the degree of engagement and non-distraction of Mobile Augmented Reality has been of major concern to scholars. This is because Mobile Augmented Reality should be a focused, movable and engaged augmented environment which can allow users to achieve the desired objectives. Thus, this paper explores Mobile Augmented Reality engagement elements that promote social acceptance among users. These elements will enable Mobile Augmented Reality designers to design apps that will be able to raise clients' engaging quality and enthusiasm for a satisfying way. The finding of this paper contends that there are 22 noteworthy components of commitment required for the structure of a drew in clients' Mobile Augmented Reality application. These 22 elements include Aesthetics, Novelty, Usability, Feedback, Motivation, Attention, Perceived Control, Curiosity, Enjoyment, Self-efficacy, Friendliness, Social skill, Endurability, Interest, Immersion, Challenge, Satisfaction, User, Autonomy, Improvement, Supportive, Trust and Interaction. This paper contends that for a productive and drew in Mobile Augmented Reality application, these 22 components are basic. It is vital for planners to consider these components in their structure so as to guarantee that their application clients are emphatically locked in. In like manner, these components guarantee that Mobile Augmented Reality application rises above past the utilization of writings and recordings shows.Â Â Â